Tainy i sud'ba Rossii . Tainy i sud'ba Rossii . Mysteries and Destiny of Russia . Тайны и судьба России - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion on the connections between Empire and revolution in Russian history. (Part 1) Contributors: Razumovskii, Feliks (Anchor) Обсуждение связи империи и революции в истории России. (Часть 1). Создатели: Разумовский, Феликс (Ведущий/Ведущая)